P-365 Pre-selected for an award: Altered endometrial oestrogen-responsiveness and aberrant expression of cell-fate markers may contribute to the aetiology of recurrent pregnancy loss. (6th August 2021) - Al-Lamee, H; Tempest, N; Drury, J; Drakeley, A; Hapangama, D
Abstract: Study question: Do women with recurrent pregnancy loss (RPL) have an aberrant expression of oestrogen receptor-β (ERβ) and cell-fate markers during the window of implantation (WOI) endometrium? Summary answer: Women with RPL are found to have significantly altered levels of ERβ and Ki-67 in the WOI endometrium, possibly resulting in anti-proliferative and anti-angiogenic effects. What is known already: RPL affects 1% of all women and has been associated with altered endometrial angiogenesis and proliferation when compared with the endometrium of healthy fertile women. RPL can be subcategorised into recurrent loss of anembryonic pregnancy, fetal loss (following evidence of a fetal heartbeat) and recurrent implantation failure (RIF). ERβ is the only oestrogen-receptor (ER) known to be expressed in the vascular endothelium of the endometrium and is the dominant ER during the WOI. It has an important role in endometrial regeneration and is proposed to regulate the angiogenic and vascular changes that occur in embryo implantation. Study design, size, duration: This pilot case-control study took place at the Liverpool Women's Hospital and included 38 women; 29 who suffered RPL and 9 controls with proven fertility (≥2 healthy pregnancies). Of the RPL group, 9 had recurrent loss of anembryonic pregnancy, 10 had recurrent fetal loss and 10 had RIF. Endometrial samples were collected during the WOI (cycle day 22+/-2). Participants/materials, setting, methods: To determine whether markers of endometrial cell proliferation and oestrogen-responsiveness are associated with RPL, we assessed the immuno-staining for ERβ, progesterone receptor (PR) and cell-fate marker Ki-67 in endometrial biopsies during the WOI using immunohistochemistry. A semi-quantitative immuno-staining score was used to assess the endometrial glands, stroma, luminal epithelium, perivascular and vascular endothelium compartments separately. Statistical differences between groups were calculated by non-parametric tests and significance level set at p < 0.05. Main results and the role of chance: During the WOI, the endometrial epithelium of women with RIF and recurrent anembryonic pregnancy loss showed significantly higher levels of ERβ when compared with fertile controls (p = 0.01 and p = 0.01, respectively). This may indicate an anti-proliferative process occurring at the site of implantation with very early pregnancy losses. In contrast, with women with recurrent fetal loss, a significantly lower level of ERβ was found within the vascular endothelium when compared with the fertile controls (p < 0.01). This supports the theory that increased oxygen levels may compromise trophoblastic invasion, thereby leading to fetal loss. The presence of Ki-67 (a marker of proliferation) was significantly lower within the vascular endothelium of all types of RPL: recurrent anembryonic loss (p = 0.02), RIF (p = 0.02) and recurrent fetal loss (p < 0.01). These findings suggest ineffective endometrial angiogenesis in RPL, resulting in a suboptimal endometrial microenvironment. PR was found to be significantly reduced (p < 0.01) in the perivascular area of women with RIF versus fertile controls. Since decidualisation and preparation of the endometrium for a successful implantation is controlled by critical target genes downstream of PR, this alteration in PR may be an important feature of their defective endometrial phenotype. Limitations, reasons for caution: Samples analysed were taken from the functional endometrium and therefore the results do not reflect the basalis. The WOI was identified using history and histological appearance, rather than timing with ovulation. Although we detected statistical significance, generalisation of the results requires further studies with larger sample size. Wider implications of the findings: This data provides novel insight into the biological correlates of clinical types of RPL and suggests that specific alterations in the regulation of endometrial cell fate and oestrogen- responsiveness are associated with different types of RPL. This highlights possible new therapies for RPL, such as selective oestrogen receptor modulators (SERMs). Trial registration number: Not applicable